2019
DOI: 10.2217/fmb-2019-0092
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine-Impregnated Catheters as a Potential Strategy to Control Biofilm-Associated Urinary Tract Infections

Abstract: Aim: This study proposes the impregnation of Foley catheters with chlorpromazine (CPZ) to control biofilm formation by Escherichia coli, Proteus mirabilis and Klebsiella pneumoniae. Materials & methods: The minimum inhibitory concentrations (MICs) for CPZ and the effect of CPZ on biofilm formation were assessed. Afterward, biofilm formation and the effect of ciprofloxacin and meropenem (at MIC) on mature biofilms grown on CPZ-impregnated catheters were evaluated. Results: CPZ MIC range was 39.06–625 mg/l. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…K. pneumoniae is a major nosocomial infection, found worldwide, that shows resistance to many commonly used antibiotics and has the ability to form biofilms on different physiological surfaces and medical devices [27][28][29][30][31]. Hence, there is a need for inhibition of the bacterial biofilm formation to control the infection, while, biologically synthesized NPs are new agents with antibiofilm activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae is a major nosocomial infection, found worldwide, that shows resistance to many commonly used antibiotics and has the ability to form biofilms on different physiological surfaces and medical devices [27][28][29][30][31]. Hence, there is a need for inhibition of the bacterial biofilm formation to control the infection, while, biologically synthesized NPs are new agents with antibiofilm activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, docking studies demonstrated that the enhanced inhibitory action of the irradiated compound was a result of the overall effect of the photoproducts on the biological target. The capability of chlorpromazine to impede the biofilm formation on urinary catheter was also demonstrated by Sidrim et al [ 59 ] in a previous work, in which this drug significantly suppressed the growth of E. coli , Proteus mirabilis , and Klebsiella. Tozar et al in 2020 examined the anti-staphylococcal activity and mode of action of thioridazine photoproducts after different periods of laser irradiation.…”
Section: Antidepressants and Antipsychoticsmentioning
confidence: 56%
“…Killing effects of antibiotics are known to be dramatically reduced in the presence of foreign bodies such as sutures and implants because bacteria form biofilms on the foreign bodies [21]. For example, catheter associated urinary tract infections are of serious concern [22]. Cells in biofilms are slow growing and thus are more resistant to antibiotics.…”
Section: Discussionmentioning
confidence: 99%